Presentation is loading. Please wait.

Presentation is loading. Please wait.

Programming Languages and Compilers (CS 421)

Similar presentations


Presentation on theme: "Programming Languages and Compilers (CS 421)"— Presentation transcript:

1 Programming Languages and Compilers (CS 421)
Sasa Misailovic 4110 SC, UIUC Based in part on slides by Mattox Beckman, as updated by Vikram Adve, Gul Agha, and Elsa L Gunter 11/10/2018

2 String with more then one parse: 0 + 1 + 0 1 * 1 + 1
Example Ambiguous grammar: <exp> ::= 0 | 1 | <exp> + <exp> | <exp> * <exp> String with more then one parse: 1 * 1 + 1 Source of ambiuity: associativity and precedence 11/10/2018

3 Disambiguating a Grammar
Given ambiguous grammar G, with start symbol S, find a grammar G’ with same start symbol, such that language of G = language of G’ Not always possible No algorithm in general 11/10/2018

4 Disambiguating a Grammar
Idea: Each non-terminal represents all strings having some property Identify these properties (often in terms of things that can’t happen) Use these properties to inductively guarantee every string in language has a unique parse 11/10/2018

5 Steps to Grammar Disambiguation
Identify the rules and a smallest use that display ambiguity Decide which parse to keep; why should others be thrown out? What syntactic restrictions on subexpressions are needed to throw out the bad (while keeping the good)? Add a new non-terminal and rules to describe this set of restricted subexpressions (called stratifying, or refactoring) Replace old rules to use new non-terminals Rinse and repeat 11/10/2018

6 Two Major Sources of Ambiguity
Lack of determination of operator precedence Lack of determination of operator assoicativity Not the only sources of ambiguity 10/4/07

7 How to Enforce Associativity
Have at most one recursive call per production When two or more recursive calls would be natural leave right-most one for right assoicativity, left-most one for left assoiciativity 10/4/07

8 Example <Sum> ::= 0 | 1 | <Sum> + <Sum>
Becomes <Sum> ::= <Num> | <Num> + <Sum> <Num> ::= 0 | 1 | (<Sum>) 10/4/07

9 Operator Precedence Operators of highest precedence evaluated first (bind more tightly). Precedence for infix binary operators given in following table Needs to be reflected in grammar 10/4/07

10 Predence in Grammar Higher precedence translates to longer derivation chain Example: <exp> ::= 0 | 1 | <exp> + <exp> | <exp> * <exp> Becomes <exp> ::= <mult_exp> | <exp> + <mult_exp> <mult_exp> ::= <id> | <mult_exp> * <id> <id> ::= 0 | 1 10/4/07

11 Disambiguating a Grammar
<exp>::= 0|1| b<exp> | <exp>a | <exp>m<exp> Want a has higher precedence than b, which in turn has higher precedence than m, and such that m associates to the left. 11/10/2018

12 Disambiguating a Grammar
<exp>::= 0|1| b<exp> | <exp>a | <exp>m<exp> Want a has higher precedence than b, which in turn has higher precedence than m, and such that m associates to the left. <exp> ::= <exp> m <not m> | <not m> <not m> ::= b <not m> | <not b m> <not b m> ::= <not b m>a | 0 | 1 11/10/2018

13 Disambiguating a Grammar – Take 2
<exp>::= 0|1| b<exp> | <exp>a | <exp>m<exp> Want b has higher precedence than m, which in turn has higher precedence than a, and such that m associates to the right. 11/10/2018

14 Disambiguating a Grammar – Take 2
<exp>::= 0|1| b<exp> | <exp>a | <exp>m<exp> Want b has higher precedence than m, which in turn has higher precedence than a, and such that m associates to the right. <exp> ::= <no a m> | <no m> m <no a>| <exp> a <no a> ::= <no a m> | <no a m> m <no a> <no m> ::= <no a m> | <exp> a <no a m> ::= b <no a m> | 0 | 1 11/10/2018

15 LR Parsing Read tokens left to right (L)
Create a rightmost derivation (R) How is this possible? Start at the bottom (left) and work your way up Last step has only one non-terminal to be replaced so is right-most Working backwards, replace mixed strings by non-terminals Always proceed so that there are no non-terminals to the right of the string to be replaced 11/10/2018

16 LR Parsing Tables Build a pair of tables, Action and Goto, from the grammar This is the hardest part, we omit here Rows labeled by states For Action, columns labeled by terminals and “end-of-tokens” marker (more generally strings of terminals of fixed length) For Goto, columns labeled by non-terminals 11/10/2018

17 Action and Goto Tables Given a state and the next input, Action table says either shift and go to state n, or reduce by production k (explained in a bit) accept or error Given a state and a non-terminal, Goto table says go to state m 11/10/2018

18 LR(i) Parsing Algorithm
Based on push-down automata Uses states and transitions (as recorded in Action and Goto tables) Uses a stack containing states, terminals and non-terminals 11/10/2018

19 LR(i) Parsing Algorithm
0. Insure token stream ends in special “end-of-tokens” symbol Start in state 1 with an empty stack Push state(1) onto stack Look at next i tokens from token stream (toks) (don’t remove yet) If top symbol on stack is state(n), look up action in Action table at (n, toks) 11/10/2018

20 LR(i) Parsing Algorithm
5. If action = shift m, Remove the top token from token stream and push it onto the stack Push state(m) onto stack Go to step 3 11/10/2018

21 LR(i) Parsing Algorithm
6. If action = reduce k where production k is E ::= u Remove 2 * length(u) symbols from stack (u and all the interleaved states) If new top symbol on stack is state(m), look up new state p in Goto(m,E) Push E onto the stack, then push state(p) onto the stack Go to step 3 11/10/2018

22 LR(i) Parsing Algorithm
7. If action = accept Stop parsing, return success 8. If action = error, Stop parsing, return failure 11/10/2018

23 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=  ( ) shift 11/10/2018

24 LR(i) Parsing Algorithm
0. Insure token stream ends in special “end-of-tokens” symbol Start in state 1 with an empty stack Push state(1) onto stack Look at next i tokens from token stream (toks) (don’t remove yet) If top symbol on stack is state(n), look up action in Action table at (n, toks) 11/10/2018

25 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=  ( ) shift 11/10/2018

26 LR(i) Parsing Algorithm
5. If action = shift m, Remove the top token from token stream and push it onto the stack Push state(m) onto stack Go to step 3 11/10/2018

27 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= ( ) shift =  ( ) shift 11/10/2018

28 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=> ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

29 LR(i) Parsing Algorithm
6. If action = reduce k where production k is E ::= u Remove 2 * length(u) symbols from stack (u and all the interleaved states) If new top symbol on stack is state(m), look up new state p in Goto(m,E) Push E onto the stack, then push state(p) onto the stack Go to step 3 11/10/2018

30 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

31 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

32 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=> ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

33 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=> ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

34 LR(i) Parsing Algorithm
6. If action = reduce k where production k is E ::= u Remove 2 * length(u) symbols from stack (u and all the interleaved states) If new top symbol on stack is state(m), look up new state p in Goto(m,E) Push E onto the stack, then push state(p) onto the stack Go to step 3 11/10/2018

35 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

36 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=> ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

37 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= <Sum>  shift => ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

38 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
= <Sum> +  shift = <Sum>  shift => ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

39 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
=> <Sum> + 0  reduce = <Sum> +  shift = <Sum>  shift => ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

40 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
<Sum>  => <Sum> + <Sum >  reduce => <Sum> + 0  reduce = <Sum> +  shift = <Sum>  shift => ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

41 Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>
<Sum>  => <Sum> + <Sum >  reduce => <Sum> + 0  reduce = <Sum> +  shift = <Sum>  shift => ( <Sum> )  reduce = ( <Sum> ) shift => ( <Sum> + <Sum>  ) reduce => ( <Sum> + 1  ) reduce = ( <Sum> +  1 ) shift = ( <Sum>  + 1 ) shift => ( 0  + 1 ) reduce = ( ) shift =  ( ) shift 11/10/2018

42 LR(i) Parsing Algorithm
7. If action = accept Stop parsing, return success 8. If action = error, Stop parsing, return failure 11/10/2018

43 Example ( ) 11/10/2018

44 Example ( ) 11/10/2018

45 Example ( ) 11/10/2018

46 Example <Sum> ( ) 11/10/2018

47 Example <Sum> ( ) 11/10/2018

48 Example <Sum> ( ) 11/10/2018

49 Example <Sum> ( ) 11/10/2018

50 Example <Sum> ( ) 11/10/2018

51 Example <Sum> ( ) 11/10/2018

52 Example <Sum> ( ) 11/10/2018

53 Example <Sum> ( ) 11/10/2018

54 Example <Sum> ( ) 11/10/2018

55 Example <Sum> ( ) 11/10/2018

56 Example <Sum> ( ) 11/10/2018

57 Example <Sum> ( ) 11/10/2018

58 Shift-Reduce Conflicts
Problem: can’t decide whether the action for a state and input character should be shift or reduce Caused by ambiguity in grammar Usually caused by lack of associativity or precedence information in grammar 11/10/2018

59 -> <Sum>  + 1 + 0 shift -> <Sum> +  1 + 0 shift
Example: <Sum> = 0 | 1 | (<Sum>) | <Sum> + <Sum>  shift -> 0  reduce -> <Sum>  shift -> <Sum> +  shift -> <Sum> + 1  reduce -> <Sum> + <Sum>  + 0 11/10/2018

60 Example - cont Problem: shift or reduce?
You can shift-shift-reduce-reduce or reduce-shift-shift-reduce Shift first - right associative Reduce first- left associative 11/10/2018

61 Reduce - Reduce Conflicts
Problem: can’t decide between two different rules to reduce by Again caused by ambiguity in grammar Symptom: RHS of one production suffix of another Requires examining grammar and rewriting it Harder to solve than shift-reduce errors 11/10/2018

62 Example  abc shift a  bc shift ab  c shift abc 
S ::= A | aB A ::= abc B ::= bc  abc shift a  bc shift ab  c shift abc  Problem: reduce by B ::= bc then by S ::= aB, or by A::= abc then S::A? 11/10/2018

63 Recursive Descent Parsing
Recursive descent parsers are a class of parsers derived fairly directly from BNF grammars A recursive descent parser traces out a parse tree in top-down order, corresponding to a left-most derivation (LL - left-to-right scanning, leftmost derivation) 11/10/2018

64 Recursive Descent Parsing
Each nonterminal in the grammar has a subprogram associated with it; the subprogram parses all phrases that the nonterminal can generate Each nonterminal in right-hand side of a rule corresponds to a recursive call to the associated subprogram 11/10/2018

65 Recursive Descent Parsing
Each subprogram must be able to decide how to begin parsing by looking at the left-most character in the string to be parsed May do so directly, or indirectly by calling another parsing subprogram Recursive descent parsers, like other top-down parsers, cannot be built from left-recursive grammars Sometimes can modify grammar to suit 11/10/2018

66 Sample Grammar <expr> ::= <term> | <term> + <expr> | <term> - <expr> <term> ::= <factor> | <factor> * <term> | <factor> / <term> <factor> ::= <id> | ( <expr> ) 11/10/2018

67 Tokens as OCaml Types + - * / ( ) <id> Becomes an OCaml datatype
type token = Id_token of string | Left_parenthesis | Right_parenthesis | Times_token | Divide_token | Plus_token | Minus_token 11/10/2018

68 Parse Trees as Datatypes
<expr> ::= <term> | <term> + <expr> | <term> - <expr> type expr = Term_as_Expr of term | Plus_Expr of (term * expr) | Minus_Expr of (term * expr) 11/10/2018

69 Parse Trees as Datatypes
<term> ::= <factor> | <factor> * <term> | <factor> / <term> and term = Factor_as_Term of factor | Mult_Term of (factor * term) | Div_Term of (factor * term) 11/10/2018

70 Parse Trees as Datatypes
<factor> ::= <id> | ( <expr> ) and factor = Id_as_Factor of string | Parenthesized_Expr_as_Factor of expr 11/10/2018

71 Parsing Lists of Tokens
Will create three mutually recursive functions: expr : token list -> (expr * token list) term : token list -> (term * token list) factor : token list -> (factor * token list) Each parses what it can and gives back parse and remaining tokens 11/10/2018

72 <expr> ::= <term> [( + | - ) <expr> ]
Parsing an Expression <expr> ::= <term> [( + | - ) <expr> ] let rec expr tokens = (match term tokens with ( term_parse , tokens_after_term) -> (match tokens_after_term with( Plus_token :: tokens_after_plus) -> 11/10/2018

73 <expr> ::= <term> [( + | - ) <expr> ]
Parsing an Expression <expr> ::= <term> [( + | - ) <expr> ] let rec expr tokens = (match term tokens with ( term_parse , tokens_after_term) -> (match tokens_after_term with ( Plus_token :: tokens_after_plus) -> 11/10/2018

74 Parsing a Plus Expression
<expr> ::= <term> [( + | - ) <expr> ] let rec expr tokens = (match term tokens with ( term_parse , tokens_after_term) -> (match tokens_after_term with ( Plus_token :: tokens_after_plus) -> 11/10/2018

75 Parsing a Plus Expression
<expr> ::= <term> [( + | - ) <expr> ] let rec expr tokens = (match term tokens with ( term_parse , tokens_after_term) -> (match tokens_after_term with ( Plus_token :: tokens_after_plus) -> 11/10/2018

76 Parsing a Plus Expression
<expr> ::= <term> [( + | - ) <expr> ] let rec expr tokens = (match term tokens with ( term_parse , tokens_after_term) -> (match tokens_after_term with ( Plus_token :: tokens_after_plus) -> 11/10/2018

77 Parsing a Plus Expression
<expr> ::= <term> + <expr> (match expr tokens_after_plus with ( expr_parse , tokens_after_expr) -> ( Plus_Expr ( term_parse , expr_parse ), tokens_after_expr)) 11/10/2018

78 Parsing a Plus Expression
<expr> ::= <term> + <expr> (match expr tokens_after_plus with ( expr_parse , tokens_after_expr) -> ( Plus_Expr ( term_parse , expr_parse ), tokens_after_expr)) 11/10/2018

79 Building Plus Expression Parse Tree
<expr> ::= <term> + <expr> (match expr tokens_after_plus with ( expr_parse , tokens_after_expr) -> ( Plus_Expr ( term_parse , expr_parse ), tokens_after_expr)) 11/10/2018

80 Parsing a Minus Expression
<expr> ::= <term> - <expr> | ( Minus_token :: tokens_after_minus) -> (match expr tokens_after_minus with ( expr_parse , tokens_after_expr) -> ( Minus_Expr ( term_parse , expr_parse ), tokens_after_expr)) 11/10/2018

81 Parsing a Minus Expression
<expr> ::= <term> - <expr> | ( Minus_token :: tokens_after_minus) -> (match expr tokens_after_minus with ( expr_parse , tokens_after_expr) -> ( Minus_Expr ( term_parse , expr_parse ), tokens_after_expr)) 11/10/2018

82 Parsing an Expression as a Term
<expr> ::= <term> | _ -> (Term_as_Expr term_parse , tokens_after_term))) Code for term is same except for replacing addition with multiplication and subtraction with division 11/10/2018

83 <factor> ::= <id>
Parsing Factor as Id <factor> ::= <id> and factor tokens = (match tokens with (Id_token id_name :: tokens_after_id) = ( Id_as_Factor id_name, tokens_after_id) 11/10/2018

84 Parsing Factor as Parenthesized Expression
<factor> ::= ( <expr> ) | factor ( Left_parenthesis :: tokens) = (match expr tokens with ( expr_parse , tokens_after_expr) -> 11/10/2018

85 Parsing Factor as Parenthesized Expression
<factor> ::= ( <expr> ) (match tokens_after_expr with Right_parenthesis :: tokens_after_rparen -> ( Parenthesized_Expr_as_Factor expr_parse , tokens_after_rparen) 11/10/2018

86 Error Cases What if no matching right parenthesis?
| _ -> raise (Failure "No matching rparen") )) What if no leading id or left parenthesis? | _ -> raise (Failure "No id or lparen" ));; 11/10/2018

87 ( a + b ) * c - d expr [Left_parenthesis; Id_token "a”; Plus_token; Id_token "b”; Right_parenthesis; Times_token; Id_token "c”; Minus_token; Id_token "d"];; 11/10/2018

88 ( a + b ) * c - d - : expr * token list = (Minus_Expr (Mult_Term
(Parenthesized_Expr_as_Factor (Plus_Expr (Factor_as_Term (Id_as_Factor "a"), Term_as_Expr (Factor_as_Term (Id_as_Factor "b")))), Factor_as_Term (Id_as_Factor "c")), Term_as_Expr (Factor_as_Term (Id_as_Factor "d"))), []) 11/10/2018

89 ( a + b ) * c – d <expr> <term> - <expr>
<factor> * <term> <term> ( <expr> ) <factor> <factor> <term> + <expr> <id> <id> <factor> <term> c d <id> <factor> a <id> b 11/10/2018

90 a + b * c – d # expr [Id_token "a”; Plus_token; Id_token "b”; Times_token; Id_token "c”; Minus_token; Id_token "d"];; - : expr * token list = (Plus_Expr (Factor_as_Term (Id_as_Factor "a"), Minus_Expr (Mult_Term (Id_as_Factor "b", Factor_as_Term (Id_as_Factor "c")), Term_as_Expr (Factor_as_Term (Id_as_Factor "d")))), []) 11/10/2018

91 a + b * c – d <expr> <term> + <expr>
<factor> < term> <expr> <id> <factor> * <term> <term> a <id> <factor> <factor> b <id> <id> c d 11/10/2018

92 ( a + b * c - d # expr [Left_parenthesis; Id_token "a”; Plus_token; Id_token "b”; Times_token; Id_token "c”; Minus_token; Id_token "d"];; Exception: Failure "No matching rparen". Can’t parse because it was expecting a right parenthesis but it got to the end without finding one 11/10/2018

93 a + b ) * c – d ( expr [Id_token "a”; Plus_token; Id_token "b”; Right_parenthesis; Times_token; Id_token "c”; Minus_token; Id_token "d”; Left_parenthesis];; - : expr * token list = (Plus_Expr (Factor_as_Term (Id_as_Factor "a"), Term_as_Expr (Factor_as_Term (Id_as_Factor "b"))), [Right_parenthesis; Times_token; Id_token "c"; Minus_token; Id_token "d"; Left_parenthesis]) 11/10/2018

94 Parsing Whole String Q: How to guarantee whole string parses?
A: Check returned tokens empty let parse tokens = match expr tokens with (expr_parse, []) -> expr_parse | _ -> raise (Failure “No parse");; Fixes <expr> as start symbol 11/10/2018

95 Streams in Place of Lists
More realistically, we don't want to create the entire list of tokens before we can start parsing We want to generate one token at a time and use it to make one step in parsing Can use (token * (unit -> token)) or (token * (unit -> token option)) in place of token list 11/10/2018

96 Problems for Recursive-Descent Parsing
Left Recursion: A ::= Aw translates to a subroutine that loops forever Indirect Left Recursion: A ::= Bw B ::= Av causes the same problem 11/10/2018

97 Problems for Recursive-Descent Parsing
Parser must always be able to choose the next action based only only the very next token Pairwise Disjointedness Test: Can we always determine which rule (in the non-extended BNF) to choose based on just the first token 11/10/2018

98 Pairwise Disjointedness Test
For each rule A ::= y Calculate FIRST (y) = {a | y =>* aw}  { | if y =>* } For each pair of rules A ::= y and A ::= z, require FIRST(y)  FIRST(z) = { } 11/10/2018

99 Example Grammar: <S> ::= <A> a <B> b
<B> ::= a <B> | a FIRST (<A> b) = {b} FIRST (b) = {b} Rules for <A> not pairwise disjoint 11/10/2018

100 Eliminating Left Recursion
Rewrite grammar to shift left recursion to right recursion Changes associativity Given <expr> ::= <expr> + <term> and <expr> ::= <term> Add new non-terminal <e> and replace above rules with <expr> ::= <term><e> <e> ::= + <term><e> |  11/10/2018

101 <expr> ::= <term> [ ( + | - ) <expr> ]
Factoring Grammar Test too strong: Can’t handle <expr> ::= <term> [ ( + | - ) <expr> ] Answer: Add new non-terminal and replace above rules by <expr> ::= <term><e> <e> ::= + <term><e> <e> ::= - <term><e> <e> ::=  You are delaying the decision point 11/10/2018

102 Example Both <A> and <B> have problems:
<S> ::= <A> a <B> b <A> ::= <A> b | b <B> ::= a <B> | a Transform grammar to: <S> ::= <A> a <B> b <A> ::-= b<A1> <A1> :: b<A1> |  <B> ::= a<B1> <B1> ::= a<B1> |  11/10/2018

103 Expresses the meaning of syntax Static semantics
Meaning based only on the form of the expression without executing it Usually restricted to type checking / type inference 11/10/2018

104 Method of describing meaning of executing a program
Dynamic semantics Method of describing meaning of executing a program Several different types: Operational Semantics Axiomatic Semantics Denotational Semantics 11/10/2018

105 Different languages better suited to different types of semantics
Dynamic Semantics Different languages better suited to different types of semantics Different types of semantics serve different purposes 11/10/2018

106 Operational Semantics
Start with a simple notion of machine Describe how to execute (implement) programs of language on virtual machine, by describing how to execute each program statement (ie, following the structure of the program) Meaning of program is how its execution changes the state of the machine Useful as basis for implementations 11/10/2018

107 Axiomatic Semantics Also called Floyd-Hoare Logic
Based on formal logic (first order predicate calculus) Axiomatic Semantics is a logical system built from axioms and inference rules Mainly suited to simple imperative programming languages 11/10/2018

108 {Precondition} Program {Postcondition}
Axiomatic Semantics Used to formally prove a property (post-condition) of the state (the values of the program variables) after the execution of program, assuming another property (pre-condition) of the state before execution Written : {Precondition} Program {Postcondition} Source of idea of loop invariant 11/10/2018

109 Denotational Semantics
Construct a function M assigning a mathematical meaning to each program construct Lambda calculus often used as the range of the meaning function Meaning function is compositional: meaning of construct built from meaning of parts Useful for proving properties of programs 11/10/2018

110 Natural Semantics Aka Structural Operational Semantics, aka “Big Step Semantics” Provide value for a program by rules and derivations, similar to type derivations Rule conclusions look like (C, m)  m’ or (E, m)  v 11/10/2018

111 Simple Imperative Programming Language
I  Identifiers N  Numerals B ::= true | false | B & B | B or B | not B | E < E | E = E E::= N | I | E + E | E * E | E - E | - E C::= skip | C;C | I ::= E | if B then C else C fi | while B do C od 11/10/2018

112 Natural Semantics of Atomic Expressions
Identifiers: (I,m)  m(I) Numerals are values: (N,m)  N Booleans: (true,m)  true (false ,m)  false 11/10/2018

113 Booleans: (B, m)  false (B, m)  true (B’, m)  b
(B & B’, m)  false (B & B’, m)  b (B, m)  true (B, m)  false (B’, m)  b (B or B’, m)  true (B or B’, m)  b (B, m)  true (B, m)  false (not B, m)  false (not B, m)  true 11/10/2018

114 Relations (E, m)  U (E’, m)  V U ~ V = b (E ~ E’, m)  b
By U ~ V = b, we mean does (the meaning of) the relation ~ hold on the meaning of U and V May be specified by a mathematical expression/equation or rules matching U and V 11/10/2018

115 Arithmetic Expressions
(E, m)  U (E’, m)  V U op V = N (E op E’, m)  N where N is the specified value for U op V 11/10/2018

116 (I::=E,m)  m[I <-- V ]
Commands Skip: (skip, m)  m Assignment: (E,m)  V (I::=E,m)  m[I <-- V ] Sequencing: (C,m)  m’ (C’,m’)  m’’ (C;C’, m)  m’’ 11/10/2018

117 (if B then C else C’ fi, m)  m’
If Then Else Command (B,m)  true (C,m)  m’ (if B then C else C’ fi, m)  m’ (B,m)  false (C’,m)  m’ 11/10/2018

118 (B,m)true (C,m)m’ (while B do C od, m’ )m’’
While Command (B,m)  false (while B do C od, m)  m (B,m)true (C,m)m’ (while B do C od, m’ )m’’ (while B do C od, m)  m’’ 11/10/2018

119 Example: If Then Else Rule
(2,{x->7})2 (3,{x->7}) 3 (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? 11/10/2018

120 Example: If Then Else Rule
(2,{x->7})2 (3,{x->7}) 3 (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})? {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

121 Example: Arith Relation
(2,{x->7})2 (3,{x->7}) 3 ? > ? = ? (2+3, {x->7})5 (x,{x->7})? (5,{x->7})? (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})? {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

122 Example: Identifier(s)
(2,{x->7})2 (3,{x->7}) 3 7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})? {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

123 Example: Arith Relation
(2,{x->7})2 (3,{x->7}) 3 7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

124 Example: If Then Else Rule
(2,{x->7})2 (3,{x->7}) 3 7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true  ? (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

125 Example: Assignment (2,{x->7})2 (3,{x->7}) 3
7 > 5 = true (2+3, {x->7})? (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true  ? {x- >7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

126 Example: Arith Op ? + ? = ? (2,{x->7})? (3,{x->7}) ?
7 > 5 = true (2+3, {x->7})? (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true ? (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

127 Example: Numerals 2 + 3 = 5 (2,{x->7})2 (3,{x->7}) 3
7 > 5 = true (2+3, {x->7})? (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true  ?{x->7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

128 Example: Arith Op 2 + 3 = 5 (2,{x->7})2 (3,{x->7}) 3
7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true ? {x->7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  ? {x->7, y->5} 11/10/2018

129 Example: Assignment 2 + 3 = 5 (2,{x->7})2 (3,{x->7}) 3
7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true  {x->7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7}) ? {x->7, y->5} 11/10/2018

130 Example: If Then Else Rule
2 + 3 = 5 (2,{x->7})2 (3,{x->7}) 3 7 > 5 = true (2+3, {x->7})5 (x,{x->7})7 (5,{x->7}) (y:= 2 + 3, {x-> 7} (x > 5, {x -> 7})true  {x->7, y->5} (if x > 5 then y:= else y:=3 + 4 fi, {x -> 7})  {x->7, y->5} 11/10/2018

131 (E,m) v (C,m[I<-v])  m’
Let in Command (E,m) v (C,m[I<-v])  m’ (let I = E in C, m)  m’ ’ Where m’’ (y) = m’ (y) for y I and m’’ (I) = m (I) if m(I) is defined, and m’’ (I) is undefined otherwise 11/10/2018

132 Example (x,{x->5})  5 (3,{x->5})  3 (x+3,{x->5})  8
(let x = 5 in (x:=x+3), {x -> 17})  ? 11/10/2018

133 Example (x,{x->5})  5 (3,{x->5})  3 (x+3,{x->5})  8
(let x = 5 in (x:=x+3), {x -> 17})  {x->17} 11/10/2018

134 Comment Simple Imperative Programming Language introduces variables implicitly through assignment The let-in command introduces scoped variables explictly Clash of constructs apparent in awkward semantics 11/10/2018

135 Interpretation Versus Compilation
A compiler from language L1 to language L2 is a program that takes an L1 program and for each piece of code in L1 generates a piece of code in L2 of same meaning An interpreter of L1 in L2 is an L2 program that executes the meaning of a given L1 program Compiler would examine the body of a loop once; an interpreter would examine it every time the loop was executed 11/10/2018

136 Interpreter An Interpreter represents the operational semantics of a language L1 (source language) in the language of implementation L2 (target language) Built incrementally Start with literals Variables Primitive operations Evaluation of expressions Evaluation of commands/declarations 11/10/2018

137 Interpreter Takes abstract syntax trees as input
In simple cases could be just strings One procedure for each syntactic category (nonterminal) eg one for expressions, another for commands If Natural semantics used, tells how to compute final value from code If Transition semantics used, tells how to compute next “state” To get final value, put in a loop 11/10/2018

138 Natural Semantics Example
compute_exp (Var(v), m) = look_up v m compute_exp (Int(n), _) = Num (n) compute_com(IfExp(b,c1,c2),m) = if compute_exp (b,m) = Bool(true) then compute_com (c1,m) else compute_com (c2,m) 11/10/2018

139 Natural Semantics Example
compute_com(While(b,c), m) = if compute_exp (b,m) = Bool(false) then m else compute_com (While(b,c), compute_com(c,m)) May fail to terminate - exceed stack limits Returns no useful information then 11/10/2018


Download ppt "Programming Languages and Compilers (CS 421)"

Similar presentations


Ads by Google